2023
DOI: 10.1098/rspb.2023.0889
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics illuminates the phylogeny of flower weevils (Curculioninae) and reveals ten independent origins of brood-site pollination mutualism in true weevils

J. Haran,
X. Li,
R. Allio
et al.

Abstract: Weevils are an unusually species-rich group of phytophagous insects for which there is increasing evidence of frequent involvement in brood-site pollination. This study examines phylogenetic patterns in the emergence of brood-site pollination mutualism among one of the most speciose beetle groups, the flower weevils (subfamily Curculioninae). We analysed a novel phylogenomic dataset consisting of 214 nuclear loci for 202 weevil species, with a sampling that mainly includes flower weevils as well as representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…This remarkably diverse host repertoire contrasts with what is expected at this taxonomic scale in most weevils, especially in this subfamily: the Curculioninae (e.g. Oberprieler et al, 2007;Hernández-Vera et al, 2019;Haran et al, 2023). Exploring the phylogenetic relationship within this group and their ancestral host plant associations is thus crucial to appreciate the role that parasitic plants may play in this unusual evolution pattern.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This remarkably diverse host repertoire contrasts with what is expected at this taxonomic scale in most weevils, especially in this subfamily: the Curculioninae (e.g. Oberprieler et al, 2007;Hernández-Vera et al, 2019;Haran et al, 2023). Exploring the phylogenetic relationship within this group and their ancestral host plant associations is thus crucial to appreciate the role that parasitic plants may play in this unusual evolution pattern.…”
Section: Introductionmentioning
confidence: 92%
“…Additional individuals were sampled in seven tribes (Anthonomini, Cionini, Curculionini, Derelomini, Erirhinini, Rhamphini and Styphlini) related to Smicronychini to serve as outgroups for phylogenetic inferences. These tribes were selected based on the most recent and comprehensive phylogenomic study of the Curculioninae subfamily (Haran et al, 2023). COI dataset -COI sequences have been extracted from AHE sequencing data using MitoFinder v1.4.1 (Allio et al, 2020).…”
Section: Coi Dataset)mentioning
confidence: 99%
“…Most recently, Haran et al (2023b), in studying phylogenetic relationships within the subfamily Curculioninae, have shown that the Derelomini is not monophyletic but comprises four, unrelated lineages. Three of these lineages correspond to the subtribes recognized by Franz (2006)-Derelomina, Notolomina, and Phyllotrogina.…”
Section: Curculionidaementioning
confidence: 99%